The Psychological (Presence – Absence) of the Father and its Relationship to Aggressive Behavior Among Primary School Students in the Center of Nineveh Governorate (College of Basic Education Research Journal, 2026)
This research aimed to identify the level of fathers' psychological presence/absence among primary school students in the center of Nineveh Governorate, and to identify the level of aggressive behavior among primary school students in the center of Nineveh Governorate. It also aimed to explore the relationship between the nature of the fathers' psychological presence/ absence and aggressive behavior among primary school students in the center of Nineveh Governorate. The researcher used a ready-made instrument (Al-Hamdani, 2024) to measure the level of fathers' psychological presence/ absence, consisting of 36 items. The researcher established the face validity of the instrument and determined its reliability using the test-retest method, which yielded a value of 0.78 with three subscales (high, medium, low). The researcher also used a ready-made instrument to measure aggressive behavior (Abdul-Fattah, 2024), consisting of 35 items. Validity and reliability were established for this instrument, yielding a value of 0.76 with three subscales (high, medium, low). The research sample consisted of 90 male and female students from schools in the center of Mosul. The results showed that the students have a high level of psychological presence of the father as a result of the father's interactive and supportive presence in their lives. The aggressive behavior of the students at this stage is an indicator of unmet psychological needs rather than an intentional deviation in behavior. Also, there is an inverse correlation between the first and second variables. The researcher reached a set of recommendations and suggestions.
Keywords: (Presence – Absence) Psychological; in relation to aggressive behavior